Dextran sodium sulfate (DSS) induces colitis in mice by forming nano-lipocomplexes with medium-chain-length fatty acids in the colon. - Hamed Laroui; Sarah A Ingersoll; Hong Chun Liu; Mark T Baker; Saravanan Ayyadurai; Moiz A Charania; Famina Laroui; Yutao Yan; Shanthi V Sitaraman; Didier Merlin (PLoS ONE, 2012)
Inflammatory bowel diseases (IBDs), primarily ulcerative colitis and Crohn's disease, are inflammatory disorders caused by multiple factors. Research on IBD has often used the dextran sodium sulfate (DSS)-induced colitis mouse model. DSS induces in vivo but not in vitro intestinal inflammation. In addition, no DSS-associated molecule (free glucose, sodium sulfate solution, free dextran) induces in vitro or in vivo intestinal inflammation. We find that DSS but not dextran associated molecules established linkages with medium-chain-length fatty acids (MCFAs), such as dodecanoate, that are present in the colonic lumen. DSS complexed to MCFAs forms nanometer-sized vesicles ~200 nm in diameter that can fuse with colonocyte membranes. The arrival of nanometer-sized DSS/MCFA vesicles in the cytoplasm may activate intestinal inflammatory signaling pathways. We also show that the inflammatory activity of DSS is mediated by the dextran moieties. The deleterious effect of DSS is localized principally in the distal colon, therefore it will be important to chemically modify DSS to develop materials beneficial to the colon without affecting colon-targeting specificity.